Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3758/s13414-019-01893-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrusions into the shadow of attention: A new take on illusory conjunctions

Abstract: We present new evidence about illusory conjunctions (ICs) suggesting that their current explanation requires revision. According to Feature Integration Theory (FIT; Treisman & Gelade Cognitive Psychology, 12, 97-136, 1980), focal attention to a single stimulus is required to bind its features into an integrated percept. FIT predicts that if attention is spread over multiple stimuli, features of these different stimuli can be combined into a single percept and produce ICs. Treisman and Schmidt (Cognitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…However, in our experiments, the number task did not modulate the proportion of illusory conjunctions in Experiment 1, in which task demands were manipulated between blocks of trials. Our results are in line with previous literature demonstrating that divided attention manipulations affect illusory conjunctions in distal but not proximal set ups (Henderson & McClelland, 2020).…”
Section: General Discussion and Conclusionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in our experiments, the number task did not modulate the proportion of illusory conjunctions in Experiment 1, in which task demands were manipulated between blocks of trials. Our results are in line with previous literature demonstrating that divided attention manipulations affect illusory conjunctions in distal but not proximal set ups (Henderson & McClelland, 2020).…”
Section: General Discussion and Conclusionsupporting
confidence: 93%
“…In contrasts, other studies have demonstrated that secondary tasks impair performance of peripheral tasks (Li et al, 2002; Matthews et al, 2018; Paul & Schyns, 2003; Treisman & Schmidt, 1982; Treisman & Gelade, 1980). However, some of these previous studies compared conditions in which participants responded to the secondary task with conditions of no response (Aru & Bachmann, 2017; Aru et al, 2018; Li et al, 2002; Matthews et al, 2018; see also Henderson & McClelland, 2020). Attentional demands are extremely different when responding vs. not responding, two conditions that differ in attentional demands, task load, response preparation, and execution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the interest in putting together a special issue is that papers can 'talk' to each other in ways that might not have occurred without their accidental proximity in the issue. So Henderson and McClelland (2020) are proposing that those attended digits in an illusory conjunction experiment are casting attentional shadows in the direction from digit to fixation (see their Figure 7). In the next article, Ceja, Jardine, & Franconeri, (2019)* present a new version of the illusory conjunction phenomenon.…”
Section: Binding Of Featuresmentioning
confidence: 99%
“…It is only under focused attention, that these components are sequentially integrated into a coherent percept. The Feature Integration Theory has been used to explain a welldescribed perceptual phenomenon, illusory conjunctions (Ashby et al, 1996;Henderson & McClelland, 2020), referring to incorrect feature groupings of two presented stimuli (Treisman & Schmidt, 1982). For instance, the perception of a red circle, following the brief presentation of a green circle alongside a red square.…”
mentioning
confidence: 99%